Change for Change - Raju, G. N. D. (Prabandhan: Indian Journal of Management, 2010)
Organizational change involves the implementation of new tools, procedures or technologies in order to face challenges due to the changing demands of business, or to create new business opportunities. Change management is yet another widely debated and written about topic in management. The last couple of decades have seen managers experiencing series of radical changes at the work place. Change is a complex process-it is a response to continuously evolving conditions. The days of stable environment and relatively few changes are over. Today we have an environment where change is not only continuous but requires the management to adopt multiple strategies to meet them. Moreover, change processes have become a kind of turning point in organizations with their vast scope leaving one with the idea that it is not the change of culture one should get used to, but to the cultural changes. Change management refers to the making of changes in a planned and managed or systematic fashion. The aim is to more effectively implement new methods and systems in an on going organization.